THE EFFECT OF PRODUCT QUALITY AND SERVICE QUALITY ON PURCHASING DECISIONS AT TOKO BAHAN KUE 55 - Halim, Enrico Glenn; Soeparto, Alexander Wahyudi Henky (Universitas Ciputra Surabaya, 2024)
Toko Bahan Kue 55 is a business engaged in retailing cake ingredients, cake suppliesand cake equipment. This study aims to determine the effect of product quality and servicequality on purchasing decisions at the Toko Bahan Kue 55. The variables involved in this studyare product quality and service quality as independent variables and purchasing decisions asdependent variables. The method used in this research is a quantitative method using multiple linear regression tests. The sample in this study were 150 consumers who had made purchases at Toko Bahan Kue 55. The results of this study indicate that product quality has a positive and significant effect on purchasing decisions at Toko Bahan Kue 55. Service quality has a positive and significant influence on purchasing decisions at Toko Bahan Kue 55.